PENGARUH PELATIHAN, PENGEMBANGAN SUMBER DAYA MANUSIA DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI PT. PLN (PERSERO) UPT PADANG - Aminar Sutra Dewi; Fuji Rahmadani (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to determine the influence of training, human resource development, and job promotion variables on the performance of employees at PT. PLN (Persero) UPT Padang. This research method utilizes a quantitative approach. Data collection techniques involve, firstly, field research such as interviews, questionnaires or surveys, observations, and documentation, and secondly, library research involving literature books with 45 respondents using total sampling technique. Respondents' data are processed using SPSS. The results of this research indicate that training, human resource development have a positive and significant whereas job promotion have a negative effect on the performance of employees at PT. PLN (Persero) UPT Padang